2015
DOI: 10.1111/jwas.12169
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding Effects on Body Weight at Harvest Size and Grow‐out Survival Rate in a Genetic Selected Population of Pacific White Shrimp Penaeus (Litopenaeus) vannamei

Abstract: The objective of this study was to investigate the effect of inbreeding on body weight (BW) at harvest size (130 d of age) and grow-out survival rate (SR) (65-130 d of age) in a nucleus breeding population of Penaeus (Litopenaeus) vannamei. An experiment was designed to generate inbred families the product of sibling matings, as well as groups of families with different inbreeding coefficients in three successive generations. The families came from a broodstock line selected for growth and survival. Inbreeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(46 reference statements)
2
5
0
Order By: Relevance
“…This study found that inbreeding had a significant negative effect on body weight and body length at harvest size (120 days of age) with an estimated effect on inbreeding coefficient. This is consistent to the estimated by Ríos-Pérez et al who found that inbreeding had a significant negative effect on the body weight at the age of 130-day stage in Penaeus (Litopenaeus) vannamei [19]. Significant inbreeding depression was found at all the inbreeding levels studied (80, 100, and 140 days), the inbreeding depression in the body weight at the 140- 7 International Journal of Genomics day stage was found to be -10.4% at F = 0:25, -16.61% at F = 0:375, and -23.68% at F = 0:50, and an increasing inbreeding depression of growth was observed with increasing inbreeding coefficient at 140-day stage in Fenneropenaeus chinensis [24].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study found that inbreeding had a significant negative effect on body weight and body length at harvest size (120 days of age) with an estimated effect on inbreeding coefficient. This is consistent to the estimated by Ríos-Pérez et al who found that inbreeding had a significant negative effect on the body weight at the age of 130-day stage in Penaeus (Litopenaeus) vannamei [19]. Significant inbreeding depression was found at all the inbreeding levels studied (80, 100, and 140 days), the inbreeding depression in the body weight at the 140- 7 International Journal of Genomics day stage was found to be -10.4% at F = 0:25, -16.61% at F = 0:375, and -23.68% at F = 0:50, and an increasing inbreeding depression of growth was observed with increasing inbreeding coefficient at 140-day stage in Fenneropenaeus chinensis [24].…”
Section: Discussionsupporting
confidence: 92%
“…Inbreeding depression for different components of fitness was occurred in animals and plants, such as fertility [43], hatchability [44], body weight [45], and survival [46]. Studies about the inbreeding depression of aquaculture species are of general concern, including Litopenaeus vannamei [19,23,47], Eulimnadia Texana [48], Penaeus (marsupenaeus) japonicas [25], Fenneropenaeus chinensis [24], and Portunus trituberculatus [20,49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heritability for SU in the observed scale was lower (0.02) than previous estimates obtained for another shrimp population (0.04–0.10) (Gitterle, Rye, et al, ), and it lies between a previous estimate for this population (0.04), reported by Campos‐Montes et al (), and that (0.01) of another population from the same hatchery (De Los Ríos‐Pérez, Campos‐Montes, Martínez‐Ortega, Castillo‐Juárez, & Montaldo, ).…”
Section: Discussionsupporting
confidence: 45%
“…ble differences in additive genetic variance of body weight between morphotypes of giant freshwater shrimp Hung, Nguyen, Hurwood, and Mather (2014). also reported morphotypes, and reproductive status of giant freshwater prawn had significant effects on estimates of genetic parameters of body weight Ellen et al (2014). reported a low-to-moderate heritability of between 0.1 and 0.4 for social interaction traits in farmed animals, suggesting possibilities of selecting these traits for better growth and survival.…”
mentioning
confidence: 85%